The relationship between macroeconomics variables towards Malaysian stock market / Nurul Ashiqin Mohd Hatta - Mohd Hatta, Nurul Ashiqin (Faculty of Business and Management, 2018)
The aim of this study is to investigate the relationship between macroeconomic variables which consist of exchange rate, interest rate and money supply towards the stock market in Malaysia represent by FTSE Bursa Malaysia KLCI Index. The study used Multiple Linear Regression in order to find the relationship among independent variables and dependent variable. The data is collected from year 2010 until 2017 and conduct in quarterly basis. From the result, it reveals that exchange rate has a negative significant relationship towards stock market (FTSE Bursa Malaysia KLCI). While interest rate is insignificant and money supply have a positive significant relationship towards (FTSE Bursa Malaysia KLCI). These results give additional understanding of the relationship between the macroeconomic variables and FTSE Bursa Malaysia KLCI and should be useful for regulator, investor and speculator.